Exploring the Free Learning Policy: Analysis of National Assessment Implementation Strategies in Elementary Schools - Dwiprabowo, Risky; Marini, Arita; Zakiah, Linda (Jurnal Elementaria Edukasia, 2024)
The need for strategies and understanding of the implementation of the National Assessment program in primary schools, especially in primary schools. Problems include suboptimal understanding of assessment goals and methods, school readiness to adopt this program, and challenges in ensuring that assessments carried out can provide an accurate picture of students' literacy and numeracy skills. So the purpose of this study is to answer the research question, namely how the strategy of implementing the national assessment at SD Negeri Baru 02 Pagi. The research method used is qualitative with a phenomenological approach that will provide an in-depth analysis of the implementation of research. The results of the analysis showed significant improvements in literacy and numeracy skills, with the most significant improvements in the ability to interpret and understand text content as well as in the domains of geometry and reasoning skills. This shows that the strategy of active student involvement in learning has had a positive impact in improving students' literacy and numeracy skills. The results obtained through the implementation of strategies that encourage proactive student involvement in the learning process have been shown to be effective in improving literacy and numeracy skills, which are key elements in the National Assessment program. The implications of these findings highlight the strategic role of effective learning strategies in achieving quality educational outcomes, and emphasize the need to apply the right approach in developing learning strategies to support the achievement of better educational goals.